Characterization and Properties of Metallic Iron Nanoparticles: Spectroscopy, Electrochemistry, and Kinetics - Nurmi, James T; Tratnyek, Paul G; Sarathy, Vaishnavi; Baer, Donald R; Amonette, James E; Pecher, Klaus; Wang, Chongmin; Linehan, John C; Matson, Dean W; Penn, R. Lee; Driessen, Michelle D (Environmental science & technology, 2005)
There are reports that nano-sized zero-valent iron (Fe0) exhibits greater reactivity than micro-sized particles of Fe0, and it has been suggested that the higher reactivity of nano-Fe0 may impart advantages for groundwater remediation or other environmental applications. However, most of these reports are preliminary in that they leave a host of potentially significant (and often challenging) material or process variables either uncontrolled or unresolved. In an effort to better understand the reactivity of nano-Fe0, we have used a variety of complementary techniques to characterize two widely studied nano-Fe0 preparations:  one synthesized by reduction of goethite with heat and H2 (FeH2) and the other by reductive precipitation with borohydride (FeBH). FeH2 is a two-phase material consisting of 40 nm α-Fe0 (made up of crystals approximately the size of the particles) and Fe3O4 particles of similar size or larger containing reduced sulfur; whereas FeBH is mostly 20−80 nm metallic Fe particles (aggregates of <1.5 nm grains) with an oxide shell/coating that is high in oxidized boron. The FeBH particles further aggregate into chains. Both materials exhibit corrosion potentials that are more negative than nano-sized Fe2O3, Fe3O4, micro-sized Fe0, or a solid Fe0 disk, which is consistent with their rapid reduction of oxygen, benzoquinone, and carbon tetrachloride. Benzoquinonewhich presumably probes inner-sphere surface reactionsreacts more rapidly with FeBH than FeH2, whereas carbon tetrachloride reacts at similar rates with FeBH and FeH2, presumably by outer-sphere electron transfer. Both types of nano-Fe0 react more rapidly than micro-sized Fe0 based on mass-normalized rate constants, but surface area-normalized rate constants do not show a significant nano-size effect. The distribution of products from reduction of carbon tetrachloride is more favorable with FeH2, which produces less chloroform than reaction with FeBH.